PKM Strengthening Organizations through Edupreneurship and the Establishment of a Cooperative for Karang Taruna Balekambang Village - East Jakarta - Prasetio ariwibowo; Tjipto Djuhartono (Jurnal SOLMA, 2020)
This community service activity aims to increase the knowledge and spirit of entrepreneurship (Edupreneurship) for the people of Balekambang - East Jakarta (specifically the Youth Organization management) and the entire Balekambang community - East Jakarta (especially the Youth Organization management) is expected to understand the principles and have a Cooperative in under the auspices of a legal entity foundation and the adoption of technology throughout the Balekambang community - East Jakarta. This training method (PKM) is in the form of entrepreneurship training, business management training (Edupreneurship). Participants (youth organization and community in Balekambang, East Jakarta) participated in this activity with enthusiasm, this was indicated by questions and responses regarding the material provided. During the training activities, in addition to participating as participants, partners played a role in providing training venues, participated in socializing training programs that would be carried out to the youth committee and community members in Balekambang, East Jakarta. So that the participation of partners is very supportive of the overall implementation of the PKM program activities.